2007
DOI: 10.1590/s0100-736x2007000500002
|View full text |Cite
|
Sign up to set email alerts
|

Revisão anatômica do seio venoso sagital dorsal no crânio de cães braquicéfalos

Abstract: Os seios venosos do crânio realizam a drenagem do cérebro e da medula espinhal, a fim de manter a homeostasia e o perfeito funcionamento do sistema nervoso central. Lesões na rede venosa cerebral podem causar déficits severos tais como hemiplegia, hemorragia, coma e morte. Os seios venosos são importantes pontos de referência para a realização de técnicas cirúrgicas de acesso ao cérebro. Este estudo visou analisar o trajeto do seio venoso sagital dorsal no crânio de cães braquicéfalos. Os animais braquicéfalos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
2
3
0
3
Order By: Relevance
“…According to the results, the geometry of the DSVS of brachycephalic animals assumed a triangular shape, as referred by (Getty and Grossman 1986;Dyce et al, 1996), and in dolichocephalic and mesocephalic animals a ''butterfly'' appearance (dilated at the ends and narrow in the middle). The results presented in this study are consistent with those of Machado et al, (2007); where the authors concluded that the distance from the center of the DSVS to the right and left walls of the vault relates directly to its width. These differences registered regarding that DSVS morphology may be associated with genetic evolution that each breed was initially submitted over time, when it was initially selected considering their primary vocations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to the results, the geometry of the DSVS of brachycephalic animals assumed a triangular shape, as referred by (Getty and Grossman 1986;Dyce et al, 1996), and in dolichocephalic and mesocephalic animals a ''butterfly'' appearance (dilated at the ends and narrow in the middle). The results presented in this study are consistent with those of Machado et al, (2007); where the authors concluded that the distance from the center of the DSVS to the right and left walls of the vault relates directly to its width. These differences registered regarding that DSVS morphology may be associated with genetic evolution that each breed was initially submitted over time, when it was initially selected considering their primary vocations.…”
Section: Discussionsupporting
confidence: 92%
“…All others craniometric points studied, presented some exceptions to their use in drawing DSVS on skull, revealing significant differences in results: for the asterion in mesocephalic, stephanion in brachycephalic, glabella in the three groups considered, and the pterion in its projection over the left hemisphere in mesocephalic and dolichocephalic, and in both hemispheres in brachycephalic. The comparative results between the three groups were irregular, which is in line with expectations; according to Machado (2007) and other authors already mentioned, the DSVS size varies directly with the width of the skull, which differs in all three groups. Concluding, the results observed with the study for the 3 types of skull considered, it allowed us to infer that: 1) DSVS presents a bigger length brachycephalic; 2) the DSVS width of initial, middle and end regions proved to be higly variable; 3) DSVS assume a triangular shape on brachycephalic and a ''butterfly'' appearance on dolicocephalic and mesocephalic; and 4) of all craniometric points selected, only the bregma can be useful in the three groups considered as a landmark for DSVS delimitation to orientate bicoronal/bifrontal, rostrotentorial/pterional, and caudotentorial/suboccipital craniotomies, avoiding this important vascular structure and decreasing the risk of the surgery.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, in the B and M groups we should consider the vault anterior area, and in the D group the vault posterior area, respectively. human medicine, there are only a few references to their location and use in veterinary medicine (Onar et al, 2001;De Machado et al, 2007;Schmidt et al, 2011;Carreira et al, 2011;Onar et al, 2012). The five craniometric points selected were quite useful to understand LCF anatomical morphology, its projection over the external skull surface, and to establish cranioencephalic relationships between the LCF and the vault.…”
Section: Discussionmentioning
confidence: 99%
“…) (Carreira, ). The TVS of the dorsal venous sinus system (Machado et al., ) consists of a thin‐walled paired structure running laterally from the confluence of the sinuses along the cerebellum tentorium margins, producing grooves in the occipital and posterior–inferior angle regions of the parietal bones (Rhoton, ). The clinical importance of the TVS is related to its function in draining blood from the brain and skull towards the maxillary veins, internal jugulars and vertebral venous plexus (Pucheu et al., ).…”
Section: Introductionmentioning
confidence: 99%